Dynamic Model-based Analysis of Oxygen Reduction Reaction in Gas Diffusion Electrodes - Röhe, Maximilian (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2024)
In this work, the first simulation model of oxygen depolarized cathodes (ODC), which are silver catalyst-based gas diffusion electrodes, is presented that considers the phase equilibrium of the gas-liquid interface and structure-related inhomogeneities in electrolyte distribution. By means of the model it has been identified that mass transport of water and ions in the liquid phase is a crucial factor for electrode performance and how it is influenced by the electrode structure.